PENGAWAS SEKOLAH PROFESIONAL: CIPTAKAN GURU BERKAPASITAS KNOWLEDGE PERSONS - Eko Supraptono Supraptono (BDK Makassar, 2022)
The existence of the School Supervisor becomes very strategic when the School Supervisor can play his role significantly in accordance with his competencies. The competencies possessed by the School Supervisor if implemented in full will have implications for the growth of the spirit and the spirit of performance and will deliver School Supervisors to increase their professionalism. The teacher hopes that there will be recognition of his existence as a person of education and given the opportunity to realize his 'pedagogical autonomy' professionally. In realizing its pedagogical autonomy, Teacher hopes to get the opportunity to realize his personal and professional performance through creative self-empowerment. Therefore it is necessary to build a discourse and paradigm thinking that the teacher has autonomy in carrying out his duties. However, the autonomous Teacher context is more directed at self-building capacity and remains in the corridor of knowledge persons. Teacher is important, because one of the characteristics of the 21st century is marked by a century of knowledge. The existence of School supervisors is still needed by teachers in motivating and facilitating the activities of teachers so that teachers become professors and professionals. Eksistensi pengawas sekolah menjadi sangat strategis manakala pengawas sekolah tersebut dapat memainkan perannya secara signifikan sesuai dengan kompetensi yang dimiliki. Kompetensi yang dimiliki oleh Pengawas Sekolah jika diimplementasikan secara paripurna maka akan berimplikasi pada tumbuhnya jiwa dan semangat kinerja dan akan menghantarkan pengawas sekolah untuk meningkatkan profesionalismenya. Guru sangat mengharapkan adanya pengakuan terhadap keberadaan dirinya sebagai pribadi insan pendidikan dan diberi peluang untuk mewujudkan 'otonomi pedagogisnya' secara profesional. Dalam mewujudkan otonomi pedagogisnya, guru berharap bisa memperoleh kesempatan dalam mewujudkan kinerja pribadi dan profesionalnya melalu pemberdayaan diri sendiri secara kreatif. Oleh sebab itu perlu dibangun wacana dan paradigma berpikir bahwa guru itu memiliki otonomi dalam melaksanakan tugasnya. Namun konteks guru otonom lebih mengarah pada kapasitas membangun (capacity building) diri dan tetap dalam koridor sosok yang berpengetahuan (knowledge persons). Hal ini penting dimiliki oleh guru, sebab salah satu ciri dari abad ke-21 ditandai dengan abad pengetahuan. Eksistensi pengawas sekolah masih tetap diperlukan oleh para guru dalam hal memotvasi dan memfasilitasi aktivitas guru agar menjadi guru yang kompeten dan profesional.